Analysis of stress-strain states of casting crane traverse - Sahirov Yurii; Artiukh Viktor; Mazur Vladlen; Vaynshtok Natalia; Reshetnikova Irina (E3S Web of Conferences, 2019)
The purpose of this paper is to analyze actual stress-strain states of casting crane traverse taking into account weight of lifted load, thermal effects and additional inertial loads. The object of the study is a pattern of stress distribution inside the traverse elements. Methodology is proposed for modeling and analyzing stress-strain states of the casting crane traverse based on strength calculations considering allowable stresses and FEM. Calculation scheme and equivalent model were developed, and FEM calculation was performed in CAD/CAE system. Regularity of stress distribution in the traverse is obtained, and possible ways to further research are identified.